2013
DOI: 10.1111/jvh.12125
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive activity and altered conventional phenotype markers/mediators of regulatory T cells in patients with self‐limiting hepatitis E

Abstract: Hepatitis E virus (HEV) is a major cause of self-limiting acute viral hepatitis in several developing countries. Elevated levels of peripheral CD4(+) CD25(+) Foxp3(+) , CD4(+) CD25(-) Foxp3(+) and rise in IL-10 in hepatitis E have been associated with the involvement of regulatory T cells (Treg). The functional role of the same is yet elusive. In the current study, we have assessed (i) Foxp3 expression by real-time PCR and by flow cytometry, (ii) the levels of antigen-specific IL-10 and TGF-β by ELISA, (iii) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Hence, we might be capturing the molecules present on the CD4 + T cells only. This theory supports our previous report of higher expression of CTLA-4, PD1, GITR, CD95, CD103, and CD73 on the CD4 + T regulatory and T effector cells of HEV patients [9]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, we might be capturing the molecules present on the CD4 + T cells only. This theory supports our previous report of higher expression of CTLA-4, PD1, GITR, CD95, CD103, and CD73 on the CD4 + T regulatory and T effector cells of HEV patients [9]. …”
Section: Discussionsupporting
confidence: 93%
“…Complying this, there are reports indicating the involvement of cytokines, chemokines, and soluble factors in self-limiting HEV infection [59]. However, up/downregulation of cytokines and soluble receptors is an indirect measurement of immune activation not revealing which immune cells are activated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunosuppressive effect of exosomes that can decrease the proliferation of T-lymphocytes (Taylor et al, 2003;Huber et al, 2005;Clayton et al, 2007) and natural killer cells (Clayton et al, 2008) or promote the differentiation of immunosuppressive cells, such as regulatory T-cells (Szajnik et al, 2010) or myeloid cells (Valenti et al, 2006) has been reported. It has been demonstrated that HEV infection causes suppressive activity and altered conventional phenotype markers of T regulatory cells (Rathod et al, 2014). It has been also demonstrated that exosomes may have a role in innate defence against respiratory pathogens and HCV (Kesimer et al, 2009;Dreux et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The gene expression analysis of selected interacting partners was performed in PBMCs isolated from HEV infected, recovered and healthy individuals using SYBR green based qPCR. Peripheral blood mononuclear cells (PBMCs) were isolated from fresh blood collected in K3 EDTA tube by Ficoll-Hypaque density gradient centrifugation (Rathod et al, 2014). Cells were re-suspended in RPMI 1640 medium (Invitrogen, USA) supplemented with 2 mmol/l l-Glutamine, 1 mmol/l sodium pyruvate and 20 g/ml of gentamycin.…”
Section: String Analysismentioning
confidence: 99%